Performance optimisation of a pharmaceutical production line by integrated simulation and data envelopment analysis. (8th November 2019) - Habibifar, Naser; Hamid, Mahdi; Bastan, Mahdi; Azar, Ahmad Taher
It seems that the use of mathematical models is not suitable for pharmaceutical production line optimisation and the use of simulation leads to better outputs and provides more flexibility than mathematical models. Therefore, in this study, a novel methodology based on the integration of simulation and data envelopment analysis is developed for performance optimisation of a pharmaceutical production line. For this purpose, first, an actual pharmaceutical production line was simulated, verified and validated. Afterwards, Data Envelopment Analysis (DEA) was developed for the scenario analysis. Finally, the weight of each indicator is identified through paired t-test. Results suggested that all the indicators are significant in the production unit. Optimisation model suggested that certain inputs and outputs had to be improved for the performance optimisation of the pharmaceutical unit. This is the first study in which an integrated simulation DEA is used for the performance optimisation of a pharmaceutical unit.